2003
DOI: 10.1108/00220410310698239
|View full text |Cite
|
Sign up to set email alerts
|

RoMEO studies 1: the impact of copyright ownership on academic author self‐archiving

Abstract: This is the first of a series of studies emanating from the UK JISC‐funded RoMEO Project (Rights Metadata for Open‐archiving) which investigated the IPR issues relating to academic author self‐archiving of research papers. It considers the claims for copyright ownership in research papers by universities, academics, and publishers by drawing on the literature, a survey of 542 academic authors and an analysis of 80 journal publisher copyright transfer agreements. The paper concludes that self‐archiving is not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 12 publications
0
38
0
Order By: Relevance
“…The problem with this historical legacy is that academics have come to assume that the copyright in their scholarly works are their own (Monotti and Ricketson, 2003;Gadd et al, 2003a;Hoorn and Van de Graaf, 2006) and have come to conflate the idea of copyright ownership with that of academic freedom itself. Packard (2002;p.287) writes, "of all the arguments against the notion of university ownership of faculty work, none is more persuasive than the notion of academic freedom."…”
Section: Is Copyright Ownership Synonymous With Academic Freedom?mentioning
confidence: 99%
See 3 more Smart Citations
“…The problem with this historical legacy is that academics have come to assume that the copyright in their scholarly works are their own (Monotti and Ricketson, 2003;Gadd et al, 2003a;Hoorn and Van de Graaf, 2006) and have come to conflate the idea of copyright ownership with that of academic freedom itself. Packard (2002;p.287) writes, "of all the arguments against the notion of university ownership of faculty work, none is more persuasive than the notion of academic freedom."…”
Section: Is Copyright Ownership Synonymous With Academic Freedom?mentioning
confidence: 99%
“…The second major study in this area was undertaken by the RoMEO project (Gadd et al, 2003a(Gadd et al, , 2003b. The authors surveyed 542 academic authors from 57 countries and found that 61% of academics thought they owned copyright in their research papers.…”
Section: Studies Of Academics Preferences Relating To Copyright Ownermentioning
confidence: 99%
See 2 more Smart Citations
“…A survey of academic staff at Monash University in 1997 performed by Monotti and Rickeston (2003) surprisingly found that respondents showed Ba considerable degree of willingness to share ownership of both research and teaching materials, or to consider this option (almost 90 per cent altogether), thus removing the possible conclusion that academic creators believe universities should have no rights in this material.Ŝ imilarly, the Jisc-funded Rights & Rewards (R&R) project (Bates et al 2007) utilised a methodology devised by the 2003 Rights Metadata in Open Archiving (RoMEO) project (Gadd et al 2003) to understand how academics wanted to protect any outputs they might make available in an open electronic environment. The R&R project focussed on e-learning materials whilst the RoMEO project focussed on research outputs.…”
Section: Reminds Us Thatmentioning
confidence: 99%